High-quality development and rural revitalization: the role of rural e-commerce - You, Qi; Yuan, Zihao; Yu, Xiao-She (Frontiers in Sustainable Food Systems, 2025)
IntroductionAs a cornerstone of China’s modernization strategy, rural revitalization (RR) plays a critical role in addressing regional imbalances and promoting inclusive development. This study explores how high-quality development (HQD), a strategic priority aimed at sustainable and efficient growth, impacts RR, with a focus on the mediating role of rural e-commerce (RE).MethodsUsing Chinese provincial panel data from 2011 to 2021, this study applies a panel quantile regression model to capture the nonlinear relationship between HQD, RE, and RR. This approach allows us to examine heterogeneous effects across different levels of RR development and identify threshold effects where applicable.ResultsFirst, HQD exhibits an inverted U-shaped relationship with RR, peaking at the 50th quantile of the RR distribution. Beyond a threshold HQD index value of 0.795, the effect becomes negative, suggesting that excessive development intensity may undermine rural progress. Second, RE significantly enhances RR only in regions with medium-to-high RR levels, indicating that enabling conditions such as infrastructure and market access are prerequisites for e-commerce to drive rural transformation. Third, the threshold effect of HQD is primarily observed in eastern China, the Yangtze River Economic Belt, and economically developed regions, revealing notable heterogeneity.DiscussionThese findings highlight the importance of context-specific policy design in promoting sustainable rural development. The nonlinear impact of HQD suggests that overly aggressive development strategies may be counterproductive, particularly in less-developed rural areas. Moreover, the conditional role of RE underscores the need for targeted investments to build foundational capacities before e-commerce can effectively contribute to rural revitalization. The regional disparities identified call for differentiated governance approaches that align with local economic structures and developmental stages. Overall, this study provides an evidence-based framework to guide more effective and regionally tailored rural development policies under China’s broader high-quality development agenda.